The influences of the Indian Ocean Dipole (IOD) on rainfall in South Aceh - Ratna Permatasari; Yopi Ilhamsyah; Syahrul Purnawan; Ichsan Setiawan; Mutia Ramadhaniaty; Sutarni Sutarni; Eko Cahyo Pristiwantoro (Depik, 2022)
This study aimed to examine the influences of the Indian Ocean Dipole (IOD) on rainfall in three districts in South Aceh. The analysis was undertaken using Dipole Mode Index (DMI) data and five years of rainfall (2016 to 2020) in West Labuhan Haji, Tapak Tuan, and Bakongan areas. This research employed a correlation analysis and the Principal Component Analysis, followed by Cluster Analysis to investigate the relationship between IOD and rainfall at the study location. The negative IOD occurred in 2016, and the positive IOD occurred in 2017, 2018, 2019, and 2020. The strongest positive DMI was in October 2019 (1.123C), while the strongest negative DMI was in July 2016 (0.661C). Generally, the sub-districts of West Labuhan Haji, Tapak Tuan, and Bakongan always have high rainfall. The highest rainfall in West Labuhan Haji was recorded in January 2017 (1014 mm/month), in Tapak Tuan in November 2017 (1073 mm/month), and in Bakongan in July 2020 (605 mm/month). The correlation between DMI and rainfall in the three locations shows different findings. Although it was very small, the IOD affected the rainfall in West Labuhan Haji, Tapak Tuan, and Bakongan. In West Labuhan Haji, the highest correlation was in lag 1 (0.188); in Tapak Tuan, the highest correlation was in lag 2 (0.156), while in Bakongan, the highest correlation was in lag 2 (-0.191). The correlations in these three locations are considered weak. Thus, the IOD is not the main factor affecting the rainfall in West Labuhan Haji, Tapak Tuan, and Bakongan. As South Aceh is located in windward, the orographic effect may influence high rainfall in this region.Keywords:DMIRainfallPrincipal component AnalysisWest Labuhan HajiTapak TuanBakongan